Antibacterial Activity of Solanum surattense Burm. F - Sheeba, E (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Ethanol extracts of Solanum surattense used in traditional medicine for treatment of various infections. The antibacterial activity detected was against Staphylococcus aureus, Streptococcus sp.; Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Shigella dysenteriae and Vibrio cholerae. The highest antibacterial activity was observed in 500μg concentration of leaf extracts of all bacteria screened except Shigella dysenteriae. The minimum zone of inhibition observed in 25μg concentration of leaf extract except Pseudomonas aeruginosa and Shigella dysenteriae. These results indicate that the extracts were bacteriostatic at higher concentrations. Keywords: Antibacterial activity; Solanum surattense; pathogenic micro organisms. DOI: 10.3126/kuset.v6i1.3278 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp 1-4